O wykorzystaniu koncepcji rezerwatu Ervinga Goffmana jako narzędzia interpretacji znaczenia przestrzeni w procesach edukacji uczniów z niepełnosprawnością = Application of Erving Hoffman`s concept of sanctuary as a tool in interpreting the meaning of space in educational processes of disabled students - Gajdzica, Zenon (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper attempts to apply the concept of sanctuary developed by Erving Go?man as a tool for describing, explaining and understanding the importance of space in educational processes of disabled students - especially in its non-segregational forms. The paper presents an analysis of the importance of space, places and territories in the processes of education of disabled students. It characterizes the problem of creating space of disabled students in inclusive and integrational education as a form of creating sanctuaries. Finally, the paper attempts to exemplify the concept by describing two assumptions of inclusive education by means of Go?man`s categories: goods, claims, stake holder, obstacle, agent.
Keywords: przestrzeń; miejsce; terytorium; Go?man, Erving (1922-1982); studenci niepełnosprawni; uczniowie niepełnosprawni; kształcenie włączające; space; place; territory; sanctuary; disabled students; inclusive education